2023
DOI: 10.1136/gutjnl-2022-328075
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloripromotes colorectal carcinogenesis by deregulating intestinal immunity and inducing a mucus-degrading microbiota signature

Abstract: ObjectiveHelicobacter pyloriinfection is the most prevalent bacterial infection worldwide. Besides being the most important risk factor for gastric cancer development, epidemiological data show that infected individuals harbour a nearly twofold increased risk to develop colorectal cancer (CRC). However, a direct causal and functional connection betweenH. pyloriinfection and colon cancer is lacking.DesignWe infected twoApc-mutant mouse models and C57BL/6 mice withH. pyloriand conducted a comprehensive analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…These changes with combination of pro-inflammatory cytokines and mucus degrading microbial signatures lead to carcinogenesis. Similar immune and epithelial alterations were described in human colon biopsies from H. pylori -infected patients[ 32 ].…”
Section: Introductionsupporting
confidence: 72%
“…These changes with combination of pro-inflammatory cytokines and mucus degrading microbial signatures lead to carcinogenesis. Similar immune and epithelial alterations were described in human colon biopsies from H. pylori -infected patients[ 32 ].…”
Section: Introductionsupporting
confidence: 72%
“…Extensive literatures have demonstrated that Alistipes promotes the development of colorectal cancer by activating the IL-6/STAT3 signaling pathway [ 64 ]. Helicobacter is involved in chronic inflammation, promoting colorectal carcinogenesis by deregulating intestinal immunity and inducing degradation of the mucosal microbiota [ 65 , 66 ]. Clostridia induces amino acid degradation in colorectal cancer [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ralser et al [ 11 ] discovered that in the Apc mutant mouse model, H. pylori infection recruited CD3+ T cells within the colon tissue epithelium, upregulated CD8+ T cells, and caused Treg cell loss and differentiation into potentially pathogenic Foxp3+ IL-17A+ T cells[ 43 ], resulting in a specific pro-inflammatory immune response. Furthermore, the research found that H. pylori might activate the STAT3 cancer pathway in colon cells, further blocking Treg cell infiltration[ 44 ], which was followed by elevated Ki67 expression and reduced intestinal barrier marker PAS[ 11 ]. This research also provides the first direct evidence of a causal link between H. pylori infection and CRC.…”
Section: Potential Carcinogenic Effect Of H Pylori ...mentioning
confidence: 99%
“…Recent study has revealed that H. pylori promotes the enrichment of Akkermansia spp. and Ruminococcus spp., which breakdown intestinal mucus, in the colon tissue of H. pylori -infected mice, resulting in a pro-inflammatory and pro-carcinogenic microbiota signature[ 11 ]. It is possible that H. pylori infection weakens the intestinal barrier.…”
Section: Potential Carcinogenic Effect Of H Pylori ...mentioning
confidence: 99%
See 1 more Smart Citation